Diagnostic role of circulating long non-coding RNA LINC00312 in patients with non-small cell lung cancer: a retrospective study - Ruoqian Zhang; Yan Jiang; Jing Gu; Xilin Zhang; Yanping Xie (BMC Cancer)
Abstract Background LINC00312 has shown to play a suppressive role in the development and progression of non-small cell lung cancer (NSCLC). However, the expression pattern and diagnostic role of circulating LINC00312 in NSCLC remain to be confused. Methods A total of 319 patients diagnosed with NSCLC and 180 healthy volunteers were enrolled from the First Affiliated Hospital of Huzhou University between January, 2022 and December, 2023. The participates were randomly assigned into the training and validation groups with a ratio of 6:4, while the remaining was named as the exosomal group. Reverse transcription-quantitative PCR (RT-qPCR) was employed to investigate the expression pattern of LINC00312 in NSCLC tissues, serum samples and cell lines. Receiver operating characteristic (ROC) curve analysis was carried out for distinguishing NSCLC from healthy volunteers. Results Here, we revealed that LINC00312 was lowly expressed in NSCLC and low LINC00312 expression manifested a poor prognosis. Additionally, compared with the healthy volunteer group, a reduction of circulating LINC00312 in patients with NSCLC was observed in both the training and validation groups. Further correlation analysis indicated that circulating LINC00312 expression was tightly associated with lymph node metastasis, cancer thrombus, spread through air space (STAS) status and pathological type. Moreover, circulating LINC00312 showed a good performance to distinguish NSCLC from healthy volunteers with a higher sensitivity and specificity values. Lastly, exosomal LINC00312 level was also decreased in NSCLC compared with in healthy volunteers. Conclusions Taken together, these data unveil that circulating LINC00312 was notably downregulated in NSCLC, offering a novel non-invasive marker for diagnosis of NSCLC.